Mulheres brasileiras: a trajetória textual e as entextualizações de duas camisetas esportivas em tempos de copa do mundo 2014 - Ferreira, Juliana Tito Rosa (2016)
Reflexive Modernity (GIDDENS, 1991) provides us the shift of focus from the center to the margin and enables discussions about gender, race, sexuality and other set of themes erased in Modernity. The plurality of subjects appears in this social subject insertion and among them Brazilian women stand out, who, during the World Cup have been portrayed as two objects of consumption in two medias. As the sponsor of the event and when launching its T-shirts, Adidas emphasizes the discursive and performative construction of a Brazilian woman built as a tourist attraction to be known. This caused some controversy which led to protests that have spread on the Internet. Within this context, this paper aims to describe the Brazilian textual trajectories of two consumption objects (T-shirts for the 2014 World Cup); to analyze three entextualizations about the consumption objects cited in the textual trajectory and to investigate entextualizations about Brazilian women who appear in the selected texts. For this purpose, the current research is based on a virtual ethnography (HINE, 2005) and was based on the conception of language as performative speech acts proposed by Austin ([1962] 1990), in rereading that Derrida ([1972] 1988) about performative speech acts on gender and sexuality studies suggested by Queer Theory (BLONDE, 2008, 2010; Butler, 2003). It also relies on the textual trajectory definition (BLOMMAERT, 2001; GUIMARÃES, 2014) and on the entextualizations assumptions by Bauman and Briggs (1999), Blommaert (2011) and Melo and Moita Lopes (2015). The data generation instrument are tree texts found on digital/online media and the Tshirts. The analysis construct is based on indexical clues proposed by Wortham (2011). The results indicate that the textual trajectory of the consumption objects is extensive because it travels through newspapers websites, blogs, variety websites, magazines and pages specifically developed for the World Cup, among others. The entextualizations are diverse, no one is in favor of launching the T-shirts objectifying women. Some blame Adidas, others the women themselves. Furthermore, we note the construction of crossbred Brazilian women seen only on sexual optics, based on the Queer Theory bias, as well as the intersection between gender (female), nationality (Brazilian) and race (dark-skinned to black).